Nutsedge (Cyperus spp.) Control in Bell Pepper (Capsicum annuum) Using Fallow-Period Weed Management and Fumigation for Two Years. (December 2014) - Miller, M. Ryan; Dittmar, Peter J.; Vallad, Gary E.; Ferrell, Jason A.
Abstract : Integrated management programs are becoming increasingly necessary for nutsedge control in the absence of methyl bromide. In 2012, field studies were established and maintained for a period of 2 yr at two locations to evaluate the additive effect of fallow programs and preplant fumigants for nutsedge control in bell pepper. The study included eight fallow programs consisting of eight combinations of glyphosate (G) and cultivation (C), and two fumigants; 1, 3-dichloropropene + chloropicrin, dimethyl-disulfide + chloropicrin, and a nontreated check. All fallow programs provided greater late-season control of nutsedge compared to the nontreated, with the greatest control of nutsedge observed with glyphosate fb (followed by) glyphosate (GG) and glyphosate fb cultivation fb glyphosate (GCG) fallow programs. Fumigation provided additional nutsedge control in single-input fallow programs. Increased marketable yield was observed in 2012 with the application of either fumigant compared to a nonfumigated control. Furthermore, increased marketable yield was observed with more intensive fallow programs in 2013. Nutsedge control in bell pepper was significantly increased when a fallow program was used in combination with other weed-management practices.